ECONOMIC LOSSES DUE TO KETOSIS IN DAIRY FARMS - V. Senthilkumar; A. Mohamed Safiullah; G. Kathiravan; M. Subramanian; K. Mani (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Ketosis is a condition marked by increased levels of circulating ketone bodies with or without the presence of the clinical signs. It causes severe economic losses through reduction in milk yield. For the study, 30 ketosis affected dairy animals (both cows and buffaloes) were selected through multistage random sampling technique from Namakkal and Karur districts of Tamil Nadu. Data were collected from the respondent farmers through personal interviews, using pretested interview schedule. The loss due to ketosis per affected cow was estimated to be Rs.1481.32. In buffalo, the cost of medicine, veterinary services, cost of supplements, loss towards reduction in milk yield and additional labour cost accounted for Rs.466.36 (32.03 per cent), Rs.251.27 (17.26 per cent), Rs.102.15 (7.02 per cent), Rs.472.80 (32.48 per cent) and Rs.163.21 (11.21 per cent), respectively. It could be extrapolated that the total economic loss in the State due to ketosis would be Rs.21.33 crores and Rs.2.64 crores in cows and buffaloes, respectively.